Training for Making Hand Sanitizer Based on Natural Materials at Housewares, Dukuh Jetak, Kudus (Indonesian Journal of Devotion and Empowerment, 2022)
The rise of the Covid-19 virus has made many people quite uneasy, especially with restrictions on every activity involving communities or community organizations. Therefore, to suppress the spread of the Covid-19 virus, the empowerment of the habit of washing or cleaning hands every time they carry out activity makes many people buy cleaning equipment such as hand soap and hand sanitizer. Knowledge of the procedures for making natural hand sanitizers is essential to provide easy and inexpensive means of self-cleaning. Dukuh Jetak, Kedungdowo Kudus Village, is an area where the community still upholds religious values so that some religious activities are still carried out during the pandemic but by complying with existing health protocols. It makes the people of Dukuh Jetak still gather to respect and enliven the culture of local wisdom preserved from generation to generation. Therefore, by organizing training activities for making hand sanitizers using natural ingredients for the people of Dukuh Jetak, Kedungdowo Village, it is hoped that in addition to increasing public skills and awareness of the importance of washing hands, it also makes the community less dependent on the availability of cleaning equipment on the market. Maraknya virus Covid-19 membuat banyak masyarakat cukup resah, apalagi dengan adanya pembatasan-pembatasan pada setiap kegiatan baik yang menyangkut komunitas atau organisasi masyarakat. Oleh karena itu, untuk menekan penyebaran virus Covid-19 diberdayakannya kebiasaan mencuci atau membersihkan tangan setiap melakukan suatu kegiatan, hal ini membuat banyak masyarakat membeli perlengkapan kebersihan seperti sabun cuci tangan dan hand sanitizer. Pengetahuan mengenai tata cara pembuatan hand sanitizer alami menjadi penting sebagai upaya menyediakan sarana kebersihan secara mandiri dengan mudah dan murah. Dukuh Jetak Desa Kedungdowo Kudus merupakan daerah yang masyarakatnya masih menjunjung tinggi nilai agama sehingga beberapa kegiatan keagamaan tetap dilaksanakan pada masa pandemi namun dengan mematuhi protokol kesehatan yang ada. Hal ini membuat masyarakat Dukuh Jetak tetap berkumpul untuk menghormati dan memeriahkan budaya kearifan lokal yang dilestarikan secara turun-temurun. Oleh karena itu, dengan penyelenggaraan kegiatan pelatihan pembuatan hand sanitizer menggunakan bahan alami kepada masyarakat Dukuh Jetak Desa Kedungdowo diharapkan selain menambah keterampilan dan kesadaran masyarakat akan pentingnya mencuci tangan, juga menjadikan masyarakat tidak terlalu bergantung terhadap ketersediaan perlengkapan kebersihan di pasaran.